Cinema 21 Movie Trailer Catalog Application Android Based - Diana Diana; Irfan Ardianto (Jurnal Komputer, Informasi dan Teknologi, 2022)
In this global era, the internet has penetrated various fields such as social, advertising, and business. With a large number of films, a film genre classification is made to assist users in finding and selecting the right films to watch. The genre in the film is the main element in a recommendation system, because with the classification of genres it can make it easier for the system to search for a film based on certain types. The string matching method, which is part of the string search process, plays an important role in getting documents that match your information needs more quickly. Simply by using a smartphone and internet access, people can enjoy various information on movie trailers. Then the problem is formulated how to make an android-based cinema 21 movie trailer catalog application with a string matching algorithm. Can improve better service to consumers, where consumers are expected to be able to access online so that consumers can find out information about movie trailers on the application.